Using Cloninger's Temperament Scales to Predict Substance‐Related Behaviors in Adolescents: A Prospective Longitudinal Study. (25th April 2013) - Hartman, Christie; Hopfer, Christian; Corley, Robin; Hewitt, John; Stallings, Michael
<x xml:space="preserve">Abstract</x> Background and Objectives We tested one of Cloninger's temperament theories – that high novelty seeking (NS), along with low harm avoidance (HA), reward dependence (RD), and persistence (PE), predicts early‐onset substance problems. Methods In a community‐based sample of 777 adolescents examined at two time points (mean age 13 and 18, respectively), we examined whether Cloninger's four temperament dimensions at wave 1 predicted five substance‐related outcomes at wave 2: age of initiation for cigarettes, alcohol, and illicit drugs, number of substance classes tried, and total number of DSM‐IV substance use disorder (SUD) symptoms. Results Cloninger's predicted temperament pattern did significantly predict the number of SUD symptoms at wave 2. For initiation of cigarettes/illicit drugs and number of substance classes tried, HA/NS/PE fit the pattern, but RD did not. For onset of alcohol, only NS and PE fit Cloninger's prediction. Results for NS and PE were most consistent. Conclusions and Scientific Significance Overall, this study provides evidence that Cloninger's theory may hold true for predicting problem use more than for predicting "use" or experimentation. In addition, youth with high novelty seeking and low persistence may find substances especially reinforcing, and identifying these youth and intervening before initiation has occurred may reduce the risk of future substance‐related problems. (Am J Addict 2013; 22:246–251)